A Model for Developing Political Training Curriculum for Political Parties in Indonesia - Azhar, Khairil; Yuliandri, Putrawan; Hartanto, H; Indrawan, Jerry (Politika: Jurnal Ilmu Politik, 2024)
This paper presents a model for developing a political training curriculum within the context of a political party in Indonesia. It underscores the importance of incorporating institutional values, system enhancement, autonomy in decision-making, and public interaction within the party. As stipulated in Indonesia’s constitution, there are two possible focuses depending on the subjects of such training either the party's administrators and cadres or the general public or community. The paper highlights the need for different teaching strategies and content, depending on the target audience, and emphasizes the necessity for both formative and summative evaluations to ensure the curriculum's ongoing relevance and effectiveness. Ultimately, it provides a blueprint for political parties to create effective, relevant political education programs, tailored to their unique objectives and the needs of their constituents.